Russian Social-Democratic Modernization Project in the Cultural and Ontological Contexts - V., Sviridkina E.; V., Mordovtseva T.; V., Bespalova T.; V., Vronskaya M.; M., Magomedov R. (Journal of History Culture and Art Research, 2018)
The article raises the relevant problem of the popularity of social democratic values in Russia and the difficulties of their ontologization in the modern political process. The modernization project of Russian statehood needs further theoretical development of the social-democratic idea in relation to Russian conditions. The axiological proximity of the social-democratic ideology to the needs of Russian society is, however, possible with regard to the pluralism of the argumentation of the basic values - freedom, social justice, equality, democracy, solidarity. The axiological pluralism makes Russian specificity acceptable in interpreting the values of social-democracy taking into account the peculiarities of the Russian historical path and the spiritual state of society. The "third way" for modern Russia is real in implementing the transformation of Russian statehood on the basis of the values of democratic socialism (social justice, equality, freedom, solidarity) and the concrete political, historical and cultural dimension of the nature of modern power.